If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -67 = 4n + 3(1 + 6n) -67 = 4n + (1 * 3 + 6n * 3) -67 = 4n + (3 + 18n) Reorder the terms: -67 = 3 + 4n + 18n Combine like terms: 4n + 18n = 22n -67 = 3 + 22n Solving -67 = 3 + 22n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-22n' to each side of the equation. -67 + -22n = 3 + 22n + -22n Combine like terms: 22n + -22n = 0 -67 + -22n = 3 + 0 -67 + -22n = 3 Add '67' to each side of the equation. -67 + 67 + -22n = 3 + 67 Combine like terms: -67 + 67 = 0 0 + -22n = 3 + 67 -22n = 3 + 67 Combine like terms: 3 + 67 = 70 -22n = 70 Divide each side by '-22'. n = -3.181818182 Simplifying n = -3.181818182
| 2n-6=4n-24 | | 2-3y=4-4y | | 5(3x+-4)-(1-3x)=75 | | 13+17=5-x | | 2(n-8)=5n+11 | | (3r-18)/12=(4r-1)/15 | | -7p+6+8p=10 | | (5.7-.8)-(4.9x-1.4)= | | -36=-6d | | 12x-4+30=10x-10 | | 0.2/8.2= | | 3(x+y)-5(x-y)= | | 15=2(15+3)-1 | | 6x+13=7x-4 | | ×/10-3=7 | | 6/5=2w | | 3x-2y=8y | | 0.2/-8.2= | | 8x-1+46=18x+5 | | 6x+32=7x+11 | | 5-3X+7(X-2)=15X+8 | | -7=2(-7+3)-1 | | (a^2/3b-1/2)^-6 | | X(x-18)=-56 | | 8y-3=x-23 | | .5h+.333h-2=2 | | 120=2(2w-12)+2w | | 6lw=384 | | R=-30p^2+400p+16000 | | 8x-70=26 | | -15/.65 | | 8x-70=24 |